The Mediterranean diet and menopausal health: An EMAS position statement. (September 2020) - Cano, Antonio; Marshall, Skye; Zolfaroli, Irene; Bitzer, Johannes; Ceausu, Iuliana; Chedraui, Peter; Durmusoglu, Fatih; Erkkola, Risto; Goulis, Dimitrios G.; Hirschberg, Angelica Lindén; Kiesel, Ludwig; Lopes, Patrice; et al.
Highlights: Globally, 985 million women are aged 50 and over, leading to increasing concerns about chronic diseases with an adverse impact. Optimization of diet is a key factor in the strategies to reduce the risk of chronic disease and to promote menopausal health. Both all-cause and cause-specific mortality are reduced by MedDiet, with the major benefits seen with cardiovascular disease. Short-term adherence to the Mediterranean diet may improve vasomotor symptoms. Abstract: Introduction: Globally, 985 million women are aged 50 and over, leading to increasing concerns about chronic conditions such as cardiovascular disease, osteoporosis, dementia, and cognitive decline, which can adversely affect quality of life and independent living. Aim: To evaluate the evidence from observational studies and randomized trials on the effects of the Mediterranean diet on short- and long-term menopausal health: estrogen deficiency symptoms, cardiovascular disease, osteoporosis, cognitive and mental health, breast cancer, and all-cause mortality. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: The Mediterranean diet is a non-restrictive dietary pattern common in the olive-growing areas of the Mediterranean basin. It may improve vasomotor symptoms, cardiovascular risk factors such as blood pressure, cholesterol and blood glucose levels, as well as mood and symptoms of depression. Long-term adherence may: improve cardiovascular risk and events, and death; improve bone mineral density; prevent cognitive decline; and reduce the risk of breast cancer and all-cause mortality.